2018
DOI: 10.1111/1442-1984.12211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on seed germination and seedling growth of the halophyte Suaeda japonica Makino

Abstract: Seed germination and seedling growth of the annual halophyte species Suaeda japonica Makino were investigated in response to variable salinity of sediment pore water. The germination percentage of S. japonica’s soft brown seeds, which are dominant among dimorphic seeds, decreased with an increase in salinity, although germination was still observed at 1200‐mM NaCl concentration. The germination percentage and germination speed observed in April were higher than those observed in December when treated with sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Salt tolerance may also differ between the seeds that differ morphologically in the species belonging to the genus Suaeda. Jiang et al (2012), Haraguchi and Matsuda (2018), and Zhao et al (2018) have reported that brown seeds are more salt tolerant than black seeds under high saline conditions in certain Suaeda species, such as S. japonica, S. splendens, and S. salsa. Moreover, Suaeda species exposed to salt stress have the potential to easily increase their resistance to osmotic stress with their osmolite accumulation (Pang et al 2016).…”
Section: Genus Suaedamentioning
confidence: 99%
“…Salt tolerance may also differ between the seeds that differ morphologically in the species belonging to the genus Suaeda. Jiang et al (2012), Haraguchi and Matsuda (2018), and Zhao et al (2018) have reported that brown seeds are more salt tolerant than black seeds under high saline conditions in certain Suaeda species, such as S. japonica, S. splendens, and S. salsa. Moreover, Suaeda species exposed to salt stress have the potential to easily increase their resistance to osmotic stress with their osmolite accumulation (Pang et al 2016).…”
Section: Genus Suaedamentioning
confidence: 99%